Analysis of the relationship between body mass index and kidney function decline in a middle-aged Japanese population: A population-based retrospective cohort study - Miki Nakamura; Chiho Yamazaki; Keiju Hiromura; Atsushi Goto; Kei Hamazaki (PLoS ONE, 2026)
Japan has one of the highest dialysis prevalence rates worldwide, resulting in substantial economic and health burdens. Although obesity is a known risk factor for the decline of kidney function, the impact of being underweight remains unclear. This study aimed to investigate the relationship between body mass index (BMI), including underweight status, and kidney function decline using health check-up data. We conducted a retrospective cohort study involving Japanese individuals aged 40–74 years in Gunma Prefecture who underwent health checkups in fiscal years 2018 and 2020. The exposure was baseline BMI, which was classified into seven categories. The primary outcome was kidney function decline, defined as a ≥ 30% reduction in estimated glomerular filtration rate (eGFR) over a two-year period. Associations between BMI and kidney function decline were assessed using multivariable logistic regression analysis, adjusting for age, sex, smoking status, alcohol consumption, blood pressure, hemoglobin A1c, lipid profile, and baseline eGFR. A total of 64,970 individuals were included in the final analysis. A U-shaped association was observed between BMI and decline in kidney function. Compared to the reference group, those with obesity (BMI = 30.0–39.9 kg/m²; odds ratio [OR]: 2.05; 95% confidence interval [CI]: 1.31–3.19) and those underweight (BMI = 14.0–18.9 kg/m²; OR: 2.09; 95% CI: 1.43–3.04) had significantly increased risk. The U-shaped association between BMI and kidney function decline suggests that both obesity and underweight status are risk factors. Health guidance should target individuals in both categories to prevent chronic kidney disease.